Guideline-recommended vs high-dose long-term opioid therapy for chronic noncancer pain is associated with better health outcomes: data from a representative sample of the German population. Issue 1 (January 2018) - Häuser, Winfried; Schubert, Tino; Scherbaum, Norbert; Tölle, Thomas
Abstract : Abstract: Recent evidence-based guidelines for long-term opioid therapy (LTOT) for chronic noncancer pain (CNCP) have defined daily morphine equivalent doses (MEQ/d) that require particular caution. The recommendation for a threshold MEQ/d is based on North American studies that have demonstrated negative health outcomes associated with high-dose LTOT for CNCP. We have conducted a retrospective cross-sectional study using an anonymized German health claims database, including 4, 028, 618 persons insured by 69 German statutory health insurances, representative of age and sex for the German population in 2014. Those receiving German guideline-recommended opioid treatments (dose <120 mg MEQ/d) for CNCP were compared with those receiving high-dose LTOT (≥120 mg MEQ/d) for selected health outcomes (risky opioid prescribing; hospital admissions due to diagnoses indicative of abuse/addiction of prescribed opioids; and health costs). The prevalence of LTOT for CNCP was 0.8%, with 9.9% receiving high-dose LTOT. Those receiving German guideline-recommended opioid treatments vs those receiving high-dose LTOT differed for the following parameters: risky opioid prescribing (combination with tranquilizers) (11.1% vs 14.3%; P < 0.001), hospital admissions because of mental and behavioral disorders due to alcohol, opioids, tranquilizers, multiple substances and intoxication by narcotic agents (1.6% vs 2.9%; P < 0.001), and total health costs (7259 vs 10, 732 Euro; P < 0.001). The difference in annual costs between the 2 groups was largely due to differences in pharmaceutical costs in the outpatient setting (2282 vs 5402 [Euro sign]; P < 0.001). These data confirm recommendations for a threshold MEQ/d for CNCP as recommended by recent opioid prescribing guidelines for CNCP. Abstract : Guideline-recommended vs high-dose long-term opioid therapy for chronic noncancer pain was associated with better health outcomes in a representative sample of the German population.